Microsurgical encapsulated resection of brachial plexus schwannoma with intraoperative neuromonitoring to preserve neurological function: 36 cases report and literature review - Jingsen Chen; Xiao Dong; Shenglong Cao; Hanghuang Jin; Haiying Hu; Taizhou (BMC Surgery)
Abstract Objective To investigate the effect of protecting neural function of microsurgical encapsulated resection of brachial plexus schwannoma with intraoperative neuromonitoring. Methods 36 patients with 36 brachial plexus schwannoma were retrospectively analyzed, who underwent surgical treatment in our department from June 2016 to December 2023. The age, gender, tumor size and location, preoperative symptoms, ultrasound and magnetic resonance imaging(MRI) findings, and postoperative functions of the patients were analyzed. Results The common symptoms of brachial plexus schwannoma were palpable masses(36/36), local tenderness(30/36), sensory changes(10/36), and positive Tinel’s sign(30/36). 11 tumors were located in the nerve roots, 10 in the trunks, 10 in the divisions and cords, and 4 in the branches, 1 intraspinal and extraspinal invasion extending from c5-c6 intervertebral foramen. Complete microsurgical encapsulated resection with intraoperative neuromonitoring was performed in all 36 patients. 6 patients developed neurogenic pain in the early postoperative period. 3 patients experienced transient postoperative motor dysfunction, which were alleviated after 6 months. According to an follow-up for at least 3 months, there were no recurrence happened in this study. Conclusions The surgical technique of microsurgical encapsulated resection of brachial plexus schwannoma with intraoperative neuromonitoring is safe and may preserve neurological function.